Nuclear alterations associated to programmed cell death in larval salivary glands of Apis mellifera (Hymenoptera : Apidae) - Silva-Zacarin, E. C. M.; Taboga, S. R. [UNESP]; Silva de Moraes, R. L. M. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The silk glands of bees are a good model for the study of cell death in insects. With the objective to detect the nuclear features during glandular regression stage, larvae at the last instar and pre-pupae were collected and their silk glands were dissected and processed for ultrastructural analysis and histologically for cytochemical and imunocytochemical analysis. The results showed that the cellular nuclei exhibited characteristics of death by atypical apoptosis as well as autophagic cell death. Among the apoptosis characteristic were: nuclear strangulation with bleb formation in some nuclei, DNA fragmentation in most of the nuclei and nucleolar fragmentation. Centripetal chromatin compaction was observed in many nuclei, forming a perichromatin halo differing from typical apoptotic nuclei. With regards to the characteristics of autophagic-programmed cell death, most relevant was the delay in the collapse of many nuclei. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: silk glands; bee; metamorphosis; cell death; nucleus; Morphology